L’arte è morta. Viva l’arte! La politicizzazione dell’estetica da Hegel a Marx - Schimmenti, Gabriele (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2022)
My paper aims at investigating the politicization of aesthetics and art that began with Hegel’s Lectures on Aesthetics or Fine Arts, by examining the aesthetic conceptions of some of the most representative members of the Young Hegelians (Bruno Bauer and Arnold Ruge) and of the young Karl Marx. Hegel did not develop a conservative aesthetic thought, but instead provided the Young Hegelians with a theory of the end of art, which is also a theory of the future of art in modernity. The Young Hegelians and the young Marx will inherit and further develop these ideas by grasping the political and revolutionary level of Hegel’s aesthetic thought, but developing different paths towards the politicization of aesthetics. Young Hegelians; Hegel’s aesthetics; End of art; Karl Marx.